Efektivitas Inovasi Pelayanan Transportasi Trans Batam Berbasis E-Government oleh Dinas Perhubungan Kota Batam - Sianturi, Roni; Dompak, Timbul (LPPM Universitas Putera Batam, 2023)
A series of efforts have been implemented by the Batam City Transportation Service in providing a number of conveniences to people who use Trans Batam Bus services, one of which is creating the Trans Batam Passenger Information System (SIP TB) application. This innovation answers the demands of the Batam City Government, in improving public services, in this case applications, where local government applications are expected to become e-government media as a means of interaction between the government and the public as well as facilitating electronic services. However, there are still deficiencies in this application where the SIP TB application has not been able to fully track the whereabouts of the Trans Batam buses because a number of buses still do not have GPS installed. This study aims to analyze the effectiveness of E-Government-based Trans Batam transportation service innovations by the Batam City Transportation Service and to analyze the factors that influence the effectiveness of E-Government-based Trans Batam transportation service innovations by the Batam City Transportation Service. This study uses a qualitative method with a descriptive approach. The results showed that the effectiveness of e-government-based Trans Batam transportation service innovations by the Batam City Transportation Service had been good